Psychosocial factors influencing the recovery of athletes with anterior cruciate ligament injury: A systematic review - te Wierike, S. C. M.; van der Sluis, A.; van den Akker-Scheek, I.; Elferink-Gemser, M. T.; Visscher, C. (Scandinavian Journal of Medicine & Science in Sports, 2013)
This review describes the psychosocial factors that affect recovery following anterior cruciate ligament (ACL) injury and reconstructive surgery in athletes. A systematic search in literature with inclusion and exclusion criteria on PubMed, PsycINFO, and Embase was performed. Articles used in this review were divided in five different parts according to the biopsychosocial model of Wiese-Bjornstal, with the addition of intervention studies. The results showed that a high internal Health Locus of Control and a high self-efficacy were useful cognitive factors to facilitate the recovery. Athletes with a low level of fear of reinjury had the best knee outcome after the injury followed by a reconstruction. In addition, athletes who returned to sport had less fear of reinjury and were more experienced and established athletes compared with athletes who did not return to sport. Furthermore, researchers showed that there was a positive relation between goal setting and adherence, which in turn yielded a positive relation with the outcome of the rehabilitation of an ACL injury. There were several psychosocial interventions that appeared to be facilitating the rehabilitation process.